3- and 5-year-olds' development of mental states understanding : a preliminary analysis of their daily conversation. - Lee, Sharon Song Song. (2010)
The developmental pattern of theory of mind in bilingual children was investigated. This study adopted the methodology done Dunn, Bretherton, and Munn (1987) by studying the utterances